Evaluation of monoaminergic levels after acute administration of standardized extract of Justicia pectoralis in mice - Teles Venâncioa, Edith; de Souza, Alana Gomes; Alves de Limaa, Klistenes; Albuquerque Jales de Carvalhoa, Michele; Alves Albuquerque de Souzaa, Denia; Souza Oliveiraa, João Victor; Almeida Moreira Leala, Luzia Kalyne; de França Fontelesa, Marta Maria (Revista Cubana de Farmacia, 2019)
Introduction: Justicia pectoralis is used as antiinflamatory, antimicrobial, bronchodilator, and sedative, and some studies have shown that it also acts in the Central Nervous System. Objective: To evaluate effects of aqueous standardized extract of Justicia pectoralis (SEJP) in the monoamine levels of animals to elucidate the underlying neurochemical mechanisms associated. Methods: Extract was administered intragastrically to male mice at single dose of 200 mg/kg at a volume of (10 mL/kg). One hour after the drug administration, the animals were sacrificed by decapitation, and the prefrontal cortex (PFC), hippocampus (HC) and striatum (ST) were dissected. The High-Performance Liquid Chromatography (HPLC) method was used for determining levels of noradrenaline (NA), dopamine (DA), 3,4-dihydroxyphenylacetic acid (DOPAC), homovanillic acid (HVA), serotonin (5-HT) and 5-hydroxyindoleacetic acid (5-HIAA). Results: The work showed that SEJP decreased DA, DOPAC, NE (p< 0.01) and 5-HT (p< 0,05) levels in the prefrontal cortex. The basal level of NE in the hippocampus was significantly reduced (p< 0.05) when compared to control group. The treatment also decreased DA (p< 0.001), DOPAC (p< 0.01) and HVA (p< 0,001) levels in the striatum. Conclusion: The findings showed that SEJP decreased the monoamines levels in the brain areas observed and suggest that Justicia pectoralis has potential clinical applications in the management of psychiatric disorders.